1991
DOI: 10.1002/kin.550230109
|View full text |Cite
|
Sign up to set email alerts
|

Propagating reaction front in ‘frozen’ phase

Abstract: It is reported and explained that the front-like reaction sustains, and its velocity is enhanced in frozen phase in the chlorite-thiosulphate system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Polythionates are well-known long-lived intermediates produced from the oxidation of thiosulfate by different oxidants, leading eventually to sulfate ion. , Their further reactions with the corresponding oxidants sometimes display fascinating kinetics and may contribute to the appearance of a rich variety of exotic nonlinear dynamical phenomena. Hexathionate, being one of the important intermediates in redox transformations or metabolism of sulfur-containing compounds in various environmental, industrial, and biological systems, , is often reported to be produced in numerous oxidation processes of thiosulfate. , It is also well-known that hexathionate is unstable in weakly alkaline conditions and degradation of the sulfur–sulfur bond eventually leads mainly to the formation of elemental sulfur and thiosulfate …”
Section: Introductionmentioning
confidence: 99%
“…Polythionates are well-known long-lived intermediates produced from the oxidation of thiosulfate by different oxidants, leading eventually to sulfate ion. , Their further reactions with the corresponding oxidants sometimes display fascinating kinetics and may contribute to the appearance of a rich variety of exotic nonlinear dynamical phenomena. Hexathionate, being one of the important intermediates in redox transformations or metabolism of sulfur-containing compounds in various environmental, industrial, and biological systems, , is often reported to be produced in numerous oxidation processes of thiosulfate. , It is also well-known that hexathionate is unstable in weakly alkaline conditions and degradation of the sulfur–sulfur bond eventually leads mainly to the formation of elemental sulfur and thiosulfate …”
Section: Introductionmentioning
confidence: 99%
“…The oscillation frequency increase has been explained by the formation of crystals and interfacial phenomena during freezing. This might be partly supported by experiments with chlorite–thiosulphate system frozen to −34°C [55]. There, a velocity of wavefronts is increased because en route to total freezing the reaction occurs only in the thin liquid layer, at the periphery of the solid domain, where concentrations of chemicals are temporarily higher.…”
Section: Introductionmentioning
confidence: 93%
“…It is generally well-known that oxidation of thiosulfate ion by different oxidizing agents leads finally to sulfate ion via formation of different polythionates as long-lived intermediates. These reactions of thiosulfate, for example, with chlorite, bromate, and periodate, exhibit several exotic nonlinear dynamical phenomena such as autocatalysis under batch condition, bistability and complex periodic and aperiodic behavior in a continuously stirred tank reactor (CSTR), and an appearance of varieties of different reaction–diffusion patterns (chemical waves and chemical reaction fronts) in unstirred system. It seems to be well-established that formation of polythionates and their further reactions with the corresponding oxidants sometimes displaying fascinating kinetics play a substantial role in the appearance of these exotic behaviors. Recently, a series of investigations confirmed that besides the sulfate ion, polythionates (such as tri-, tetra-, and pentathionate) and chlorine dioxide are also produced during the oxidation of thiosulfate by chlorite ion.…”
Section: Introductionmentioning
confidence: 99%